A roadmap for strengthening evidence-informed health policy-making in Iran: protocol for a research programme - Haniye Sadat Sajadi; Reza Majdzadeh; Bahareh Yazdizadeh; Farideh Mohtasham; Mahsa Mohseni; Leila Doshmangir; John Lavis (BMC, 2019)
Abstract Background Many initiatives have been taken in the Islamic Republic of Iran to promote evidence-informed health policy-making (EIHP). However, these initiatives are not systematic. Since the implementation of EIHP is not consistent and the interventions in this regard are complex, a comprehensive plan could be a useful tool for employing initiatives to achieve and promote EIHP. Hence, this study aims to develop a roadmap for strengthening EIHP over a 3-year period in Iran. Methods Nine projects will be conducted to define the roadmap for strengthening EIHP. These projects include two reviews and a stakeholder analysis to identify the factors that facilitate or hinder achieving EIHP. The next study will be a qualitative study to prioritise the challenges and outline the main causes. The following steps will be a review of reviews to extract global experiences on interventions used for strengthening EIHP and two qualitative studies to examine the adoption of these interventions and develop an operational plan for strengthening EIHP in Iran. The research will be completed through conducting two qualitative-quantitative studies to design a tool for measuring EIHP and assessing EIHP in Iran at baseline. Discussion This national EIHP roadmap will surely be able to identify the gaps and bumps that might exist in the implementation plan for establishing EIHP and eliminate them as needed in the future. This roadmap can be a step in moving towards transparency and accountability in the health system and as thus towards good governance and improvement of the health system's performance. Although the plan can be a good model for developing countries and may promote the use of evidence in health policy-making, we should assume that there are some critical contextual factors that could potentially hinder the complete and successful implementation of EIHP. Thus, to enhance EIHP in these countries with a policy-making context that does not fully support the use of evidence, it is crucial to think about not only those interventions that directly address the EIHP barriers, but also some long-term strategies to make required changes in the context, both beyond and within the health system.